Berechnung der Erwärmung ebener Leiteranordnungen bei Stromverdrängung und Magnetisierung - Braisch, Dieter (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2010)

Comparing Partial Discharge Inception Voltage for Synthetic Ester and Gas-to-Liquid Insulation Liquids under Lightning Impulse Voltage Using a Transformer Design-Based Test Setup - Müller, Stephan; Braisch, Dieter; Luther, Matthias; Gamil, Ahmed; Schatzl, Franz; Milone, Marco (21st IEEE International Conference on Dielectric Liquids, 2022)
This article describes a test setup and the results of comparing the partial discharge inception voltage of synthetic ester and gas-to-liquid insulation liquids under lightning impulse voltage of positive polarity. The design of the test samples is chosen to simulate a common insulation arrangement of power transformers: a paper-insulated U-shaped copper winding rod vis-`a-vis a copper plane in insulation liquid with a gap between them. Partial discharges are detected via the occurrence of streamers and optical measurement thereof using fluorescent fibre optics, a photomultiplier tube and, an oscilloscope. The results are evaluated by field strength using conversion factors obtained by a finite element method simulation.<br

Comparing Synthetic Ester and Gas-to-Liquid Insulation Liquids Under Lightning Impulse Voltage Using a Creepage Discharge Test Setup - Müller, Stephan; Braisch, Dieter; Luther, Matthias; Gamil, Ahmed; Schatzl, Franz; Milone, Marco (The 7th International Advanced Research Workshop on transformers, 2022)

Compensation, Stability and Losses in the Presence of Wheeling Transactions with use of FACTS devices - Braisch, Dieter; Herold, Gerhard; et al. (PowerTech Budapest '99, 1999)
UnivIS-Import:2015-04-16:Pub.1999.tech.IE.leen.compen

Current Transformer Behaviour in the Presence of Short-Circuit Currents - Braisch, Dieter; Herold, Gerhard; et al. (Short-Circuit Currents in Power Systems, 2000)
UnivIS-Import:2015-04-16:Pub.2000.tech.IE.leen.curren

Hochgenaue und EMV-sichere Messdatenerfassung für Hochstromanlagen - Weindl, Christian; Braisch, Dieter; et al. (Bulletin SEV/VSE, 2005)
UnivIS-Import:2015-03-09:Pub.2005.tech.IE.leen.hochge

Influence of Remanent Magnetization on the Accuracy of Industry Typical Metering Current Transformers - Freiburg, Michael; Mayhofer, Christoph; Braisch, Dieter; Koch, Norbert; Bürger, Roland (58th International Universities Power Engineering Conference, 2023)

Instrument Transformer Dimensioning: Past and Future - Jäger, Johann; Braisch, Dieter; et al. (4th GCC CIGRE International Conference, 2008)
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.leen.instru

Integrated Production Umbilicals (IPU's): a Cost-Effective Solution - Heggdal, Ole; Parman, David; Braisch, Dieter; Voet, Marc; Karunakaran, Daniel; Olsen, Geir; Lassabliere, Jacques (2001 Offshore Technology Conference, 2001)

Integrated Production Umbilicals (IPU's): a Cost-Effective Solution for Subsea Tie Backs and Deepwater Developments - Braisch, Dieter; Heggdal, Ole; Parman, David; Voet, Marc; Karunakaran, Daniel; Olsen, Geir; Lassabliere, Jacques (2001 Offshore Technology Conference, 2001)
UnivIS-Import:2019-08-15:Pub.2001.tech.IE.leen.integr

Investigation of Partial Discharge Inception for Synthetic Ester and Gas-to-Liquid Insulation Liquids under Lightning Impulse Voltage using Conductor-Plate Setup with Gap or Creepage Path - Braisch, Dieter; Gamil, Ahmed (The 7th International Advanced Research Workshop on transformers, 2022)

Partial Saturation of Current Transformers in Gas Insulated Switchgears - Braisch, Dieter; Schichler, Uwe; Schumacher, Martin; Funk, Hans-Werner; Krebs, Rainer (Proceedings of the 16th International Symposium on High Voltage Engineering, 2009)

Phase-to-Phase Influence – a Design Challenge for Current Transformers in Gas Insulated Switchgears - Braisch, Dieter; Schichler, Uwe; Schumacher, Martin; Funk, Hans-Werner; Krebs, Rainer (6th Southern Africa Regional Conference, 2009)

Stabilität von Netzen mit UPFC für Durchleitungen und Abschirmung mittels elektronischem Zaun - Braisch, Dieter; Herold, Gerhard; et al. (Wirtschaftliche und technische Herausforderungen liberalisierter Strommärkte, 1999)
UnivIS-Import:2015-04-16:Pub.1999.tech.IE.leen.stabil

Transient Behaviour of High Impedance Protection Applications using for Networks with Distributed Generation - Jäger, Johann; Braisch, Dieter; Ramold, Mathias; Li, Shang; Krebs, Rainer (2005 IEEE St. Petersburg PowerTech, 2005)
The presented paper is dealing with protection principles which are preferable applied to networks with distributed generation (DG). A basic physical explanation of the high-impedance protection principle in relation to the low-impedance principle will be given considering the transient behaviour in particular. It can be shown that special requirements on the protection co-ordination for networks with DG can be covered by the high-impedance protection principle. Measurement results of a high current lab confirm the favourable behaviour of the high-impedance protection principle. It was also possible to investigate the transient behaviour of the high-impedance principle under extreme conditions like CT remanence effects. A close correlation between digital simulation and measurement results of the transient behaviour could be achieved during the investigations.
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.leen.transi
Keywords: Digital simulations; Distributed generation; High-impedance protection; Measurements; Transient behaviour